COMPUTERIZED TEST CONTROL IN THE FINAL EVALUATION OF STUDYING RESULTS - Shakotko, Віктор (Journal of Information Technologies in Education (ITE), 2022)
The aim of the study was to identify the main factors influencing the effectiveness of learning evaluation outcomes during the final control and state certification of pedagogical college graduates to build a model of quality assurance in education. All the students of three fields of study (Preschool Education, Primary Education, Secondary Education (Physical Education)) and 136 lecturers at Anton Makarenko Pedagogical College of Kremenchuk took part in the study during ten years. The total number of students who participated in the experiment exceeded 1.5 thousand people. The final assessment was organized using tests of three levels of difficulty. At various stages of the study the results were processed using correlation, multivariate and other types of analysis, which allowed the correction of the course of the experiment. A conclusion, based on these results, was made about the significant influence of psychological, pedagogical and instrumental factors either on the process or the effectiveness (objectivity) of the computerized evaluation system. The negative impact of these factors can be partially offset by taking into account the recommendations for planning, conducting and analyzing the results of computerized test control, which were developed based on the results of the study. The incompleteness of the research is pointed out, especially in the issues of reducing the influence of subjective factors and the prospects of its continuation in the direction of increasing the validity of the specified evaluation system, development of integration competence and professionally oriented tests are substantiated.